2020
DOI: 10.3390/insects11010041
|View full text |Cite
|
Sign up to set email alerts
|

ColEval: Honeybee COLony Structure EVALuation for Field Surveys

Abstract: Methods for the evaluation and comparison of the structure of numerous honeybee colonies are needed for the development of applied and fundamental field research, as well as to evaluate how the structure and activity of honeybee colonies evolve over time. ColEval complements existing methods, as it uses an online reference image bank for (human) learning and training purposes. ColEval is based on the evaluation of the surface area percentage occupied by different components of a honeybee colony: adult worker b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Each colony was placed over an individual pallet, and the pallet with its colony was lifted for 30 s. This enabled us to weigh each colony on-site without displacing or opening it and with no other intervention except when smoking was necessary. (ii) Colonies were evaluated with the ColEVaL method, a quantitative description of adult honeybees and brood surface (Hernandez et al 2020) (data not shown). The weighing method and ColEval were designed to exert minimum stress on honeybee colonies.…”
Section: Methodsmentioning
confidence: 99%
“…Each colony was placed over an individual pallet, and the pallet with its colony was lifted for 30 s. This enabled us to weigh each colony on-site without displacing or opening it and with no other intervention except when smoking was necessary. (ii) Colonies were evaluated with the ColEVaL method, a quantitative description of adult honeybees and brood surface (Hernandez et al 2020) (data not shown). The weighing method and ColEval were designed to exert minimum stress on honeybee colonies.…”
Section: Methodsmentioning
confidence: 99%
“…Colony dynamics were monitored using the ColEval method [42]. The number of bees, the number of open and capped brood cells, and the quantity of honey and pollen were estimated on average once a month across the whole beekeeping season (from March to October).…”
Section: Colony and Mite Monitoringmentioning
confidence: 99%
“…Colony dynamics was monitored using the ColEval method [41]. The number of bees, the number of open and capped brood cells, and the quantity of honey and pollen were estimated on average once a month across the whole beekeeping season.…”
Section: Colony and Mite Monitoringmentioning
confidence: 99%